Answer;
We can have the equation as;
![\begin{gathered} y\text{ = 3x} \\ \text{if y = -6, then x = -2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nw5xjpfx0ml8p9zg10qap6vmqcnrmrcmmv.png)
where 3 is k which is the proportionality constant
Explanation;
Firstly, we need to understand the relation of being directly proportional
When two variables are proportional, the relationship between them is of the nature;
![y\text{ = kx}](https://img.qammunity.org/2023/formulas/mathematics/college/mmhxvnm9il3dxouw944ut4tu97cnc1h82s.png)
where K is the proportionality constant
We can have k as 3, and that means we have the relationship as;
![y\text{ = 3x}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9soe3gxs2h4syuq3h22x3bgvfx6p4uyzi5.png)
So, from the question, x is ? and y = -6; we can have x calculated as;
![\begin{gathered} -6\text{ = 3x} \\ x\text{ = }(-6)/(3) \\ x\text{ = -2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/w2fz1bwfmrnltt9f50geejy3ffu4ywyn1g.png)